Cyprus’ Road to European Union Accession: Missed Opportunities to Promote a Cyprus Solution - Lindley, Dan (Études helléniques / Hellenic Studies, 2003)
The author argues herein that the twin tasks of the pursuit of European Union accession for Cyprus and the search for a Cyprus solution combine to present all concerned states and organizations with a number of contradictory strategic problems. These problems have been nearly impossible to surmount. Nonetheless, the short term deals and political logrolling that characcerized the European Union's approach to Cyprus accession foreclosed strategizing about how to use the EU's leverage to help resolve the Cyprus problem. Furrher, Cyprus' accession is only one-third of the problem faced by the EU, the UN, and those concerned with Aegean affairs. The status of North Cyprus must be resolved, and Turkey must be tied to the West through accession to the EU. The Republic of Cyprus will be in the EU, but much remains to be done.